Rheological behavior characterization of natural rubber containing different gel - Saengchao Thongseenuch (2018)
This research, natural rubber containing different gel contents were prepared by deproteinization and saponification treatment from high ammonium natural rubber latex. Deproteinization natural rubber was further treated as acetone extraction and then transesterification. It was founded that gel content and molecular weights of treated natural rubber were decreased and almost absented for transesterification treatment. Rheological respond on small amplitude oscillating shear (SAOS) and large amplitude oscillating shear (LAOS) deformation of treated natural rubber were captured by using rubber process analyzer (RPA 2000). Firs harmonic rheological properties, storage modulus, G′ and loss modulus, G″ decreased as gel content and molecular weight decreased. It was believed that gels, explicitly branching points, were destroyed after the natural rubber was deproteinized, transesterification, or saponification according to the molecular structure of natural rubber presumed by Tanaka et al, which functional groups contain protein and fatty acid are participated in branching to forming gel structure. It was concluded that gel content as the same as molecular structure of natural rubber could be characterized as rheological behavior. © (2014) Trans Tech Publications, Switzerland.